Parents' Efforts to Limit Gadgets by Implementing Positive Discipline from an Early Age - Maya Nurfadhillah; Hamid Patilima (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
In the contemporary digital landscape, parents grapple with challenges surrounding their children's gadget use. This qualitative study delves into how parents employ positive discipline to address the impact of gadgets on 5-6-year-olds. Through interviews with five parents, the research uncovers insights into parental strategies. Positive reinforcement, including positive stories, emerges as a key mediation tool. Agreements were reached, designating specific weekend timeframes for gadget use, though challenges related to parental consistency were noted. Discipline measures ranged from verbal reprimands to physical consequences, while rewards included praise and tangible gifts. Despite inconsistent agreement adherence, positive changes were observed in children's behaviour, reflecting increased politeness, gentleness, obedience, and enhanced creativity. This research sheds light on the dynamics of parental efforts to navigate gadget-related challenges and emphasizes the role of positive discipline in shaping children's behaviour in the digital age